Differences in the contributions of sex linkage and androgen regulation to sex‐biased gene expression in juvenile and adult sticklebacks. (2nd July 2020) - Kitano, Jun; Kakioka, Ryo; Ishikawa, Asano; Toyoda, Atsushi; Kusakabe, Makoto
Abstract: Different evolutionary interests between males and females can lead to the evolution of sexual dimorphism. However, intersex genetic correlations due to the shared genome can constrain the evolution of sexual dimorphism, resulting in intra‐locus sexual conflict. One of the mechanisms resolving this conflict is sex linkage, which allows males and females to carry different alleles on sex chromosomes. Another is a regulatory mutation causing sex‐biased gene expression, which is often mediated by gonadal steroids in vertebrates. How do these two mechanisms differ in the contributions to the resolution of intra‐locus sexual conflict? The magnitude of sexual conflict often varies between the juvenile and adult stages. Because gonadal steroids change in titre during development, we hypothesized that gonadal steroids play a role in sexual dimorphism expression only at certain developmental stages, whereas sex linkage is more important for sexual dimorphism expressed throughout life. Our brain transcriptome analysis of juvenile and adult threespine sticklebacks showed that the majority of genes that were sex‐biased in both stages were sex‐linked. The relative contribution of androgen‐dependent regulation to the sex‐biased transcriptome increased and that of sex linkage declined in adults compared to juveniles. The magnitude of the sex differences was greater in sex‐linked genes than androgen‐responsive genes, suggesting that sex linkage is more effective than androgen regulation in the production of large sex differences in gene expression. Overall, our data are consistent with the hypothesis that sex linkage is effective in resolving sexual conflict throughout life, whereas androgen‐dependent regulation can contribute to temporary resolution of sexual conflict. Abstract : Sex linkage and androgen‐dependent regulation are two main mechanisms underlying sexual dimorphism in the vertebrates. Investigating sex‐biased gene expression in juvenile and adult stickleback brains, it has been shown that gonadal steroids play a role in sexual dimorphism expressed at adult stages, whereas sex linkage is more important for sexual dimorphism expressed throughout life.